Intercountry and intracountry variations in opinions of palliative care specialist physicians in Germany, Italy, Japan and UK about continuous use of sedatives: an international cross-sectional survey. Issue 4 (22nd April 2022) - Morita, Tatsuya; Kawahara, Takuya; Stone, Patrick; Sykes, Nigel; Miccinesi, Guido; Klein, Carsten; Stiel, Stephanie; Hui, David; Deliens, Luc; Heijltjes, Madelon T; Mori, Masanori; Heckel, Maria; et al.
Abstract : Objectives: To explore intercountry and intracountry differences in physician opinions about continuous use of sedatives (CUS), and factors associated with their approval of CUS. Settings: Secondary analysis of a questionnaire study. Participants: Palliative care physicians in Germany (N=273), Italy (N=198), Japan (N=334) and the UK (N=111). Primary and secondary outcome measures: Physician approval for CUS in four situations, intention and treatment goal, how to use sedatives and beliefs about CUS. Results: There were no significant intercountry or intracountry differences in the degree of agreement with statements that (1) CUS is not necessary as suffering can always be relieved with other measures (mostly disagree); (2) intention of CUS is to alleviate suffering and (3) shortening the dying process is not intended. However, there were significant intercountry differences in agreement with statements that (1) CUS is acceptable for patients with longer survival or psychoexistential suffering; (2) decrease in consciousness is intended and (3) choice of neuroleptics or opioids. Acceptability of CUS for patients with longer survival or psychoexistential suffering and whether decrease in consciousness is intended also showed wide intracountry differences. Also, the proportion of physicians who agreed versus disagreed with the statement that CUS may not alleviate suffering adequately even in unresponsive patients, was approximately equal. Regression analyses revealed that both physician-related and country-related factors were independently associated with physicians' approval of CUS. Conclusion: Variations in use of sedatives is due to both physician- and country-related factors, but palliative care physicians consistently agree on the value of sedatives to aid symptom control. Future research should focus on (1) whether sedatives should be used in patients with longer survival or with primarily psychoexistential suffering, (2) understanding physicians' intentions and treatment goals, (3) efficacy of different drugs and (4) understanding the actual experiences of patients receiving CUS.